Autosomal recessive spastic ataxia of Charlevoix-Saguenay: a family report from South Brazil - Burguêz, Daniela; Oliveira, Camila Maria de; Rockenbach, Marcio Aloísio Bezerra Cavalcanti; Fussiger, Helena; Vedolin, Leonardo Modesti; Winckler, Pablo Brea; Maestri, Marcelo Krieger; Finkelsztejn, Alessandro; Santorelli, Filippo Maria; Jardim, Laura Bannach; Saute, Jonas Alex Morales (Arquivos de Neuro-Psiquiatria, 2017)
Autosomal recessive spastic ataxia of Charlevoix-Saguenay (ARSACS) is an early-onset, neurodegenerative disorder caused by mutations in SACS, firstly reported in Quebec, Canada. The disorder is typically characterized by childhood onset ataxia, spasticity, neuropathy and retinal hypermyelination. The clinical picture of patients born outside Quebec, however, is often atypical. In the present article, the authors describe clinical and neuroradiological findings that raised the suspicion of an ARSACS diagnosis in two female cousins with Germanic background from Rio Grande do Sul, Brazil. We present a review on the neuroimaging, ophthalmologic and neurophysiologic clues for ARSACS diagnosis. The early-onset, slowly progressive, spastic-ataxia phenotype of reported patients was similar to ARSACS patients from Quebec. The SACS sequencing revealed the novel homozygous c.5150_5151insA frameshift mutation confirming the ARSACS diagnosis. ARSACS is a frequent cause of early onset ataxia/spastic-ataxia worldwide, with unknown frequency in Brazil.
Keywords: cerebellar ataxia; spastic paraparesis; genetics; magnetic resonance imaging; ophthalmology